Yttrium aluminum garnet powder and method for synthesizing same

JP7640722B2Active Publication Date: 2025-03-05MATERION CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023545905
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-29
Filing Date
2022-01-28
Publication Date
2025-03-05
Estimated Expiration
2042-01-28

Smart Images

  • Figure 0007640722000003
    Figure 0007640722000003
  • Figure 0007640722000004
    Figure 0007640722000004
  • Figure 0007640722000005
    Figure 0007640722000005
Patent Text Reader

Abstract

A method of synthesizing yttrium aluminum garnet (YAG) powder. The method includes introducing powders of yttria and silica to form a powder mixture, where no alumina is added to the powder mixture. Milling the powder mixture in the presence of alumina grinding media and a solvent forms a powder slurry. Processing the powder slurry forms a green compact. Sintering the green compact in air at a temperature between 1100° C. and 1650° C. for greater than 8 hours to 50% or less of theoretical density forms a YAG compact that is at least 92% by weight Y3Al5O12. Milling the YAG compact without grinding media and drying produces a YAG powder. The method further includes introducing a dopant to the powder mixture to produce a doped YAG powder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Priority

[0001] This application is related to and claims priority to U.S. Provisional Patent Application No. 63 / 143,605, filed January 29, 2021, which is incorporated herein by reference.

[0002] This disclosure relates to the synthesis of yttrium aluminum garnet (YAG) powder and processing methods to produce YAG powder with controlled dopant concentrations. [Background technology]

[0003]

[0003] Yttrium aluminum garnet (YAG, yttrium aluminate, Y) doped with suitable ions 3 Al 5 O 12 ) or YAG are used in a wide variety of applications such as solid-state lasers, as phosphors in projectors, solid-state lighting, head-up displays, professional lighting, cathode ray tubes, light emitting diodes, and scintillators, among others.

[0004]

[0004] Conventional methods for making YAG powder include chemical co-precipitation, mixed precipitation, glycine-nitrate, citrate, dissolving yttria in alumina sol, amorphous form, inductively coupled thermal plasma synthesis, hydrothermal, nano powder processing, microwave coupling, among others, as exemplary routes. However, the resulting powders produced by the above mentioned techniques are expensive, time consuming to manufacture, require small batch sizes, and may have environmental downsides associated with the process as well. Furthermore, the resulting impurity levels may be lower than those required in some applications. This places a significant and unnecessary demand on resources. Summary of the Invention [Problem to be solved by the invention]

[0005]

[0005] While many methods are available for making YAG powder, there is a need for an uncomplicated solid-state powder synthesis process that provides improved yields and sinterability at lower temperatures than conventional solid-state synthesized powders while providing controlled levels of dopants, secondary or subphases and / or impurities. [Means for solving the problem]

[0006] In one embodiment, the present disclosure relates to a method for synthesizing yttrium aluminum garnet (YAG) powder. The method includes mixing yttria and silica powders to form a powder mixture. The powder mixture is alumina-free. The powder mixture may include a dopant. The method may further include ball milling, spray drying, compacting, calcining, and milling to form the YAG powder. The ball milling of the powder mixture may be performed in the presence of alumina grinding media and a solvent to form a powder slurry. The powder slurry may be spray dried to form a spray-dried powder. The spray-dried powder may be compacted to 35% or less of theoretical density to form a green compact. The green compact may be calcined in air to 50% or less of theoretical density to form a YAG compact. Milling the YAG compact without grinding media and then drying can produce YAG powder. The yttria powder can have a purity of 2N or higher, or a purity of 3N or higher. The silica can be 0.1% to 0.3% by weight based on the total weight of the powder mixture. The silica can be fumed silica. The alumina grinding media can be 95.0 to 99.8% Al 2 O 3 The purity may be

[0007]

[0007] The step of mixing to form a powder mixture may further include a dopant comprising a lanthanide or transition metal. The lanthanide or transition metal may be in the form of a compound, the compound being an oxide, a hydrate, a nitrate, a chloride, or a combination thereof. The lanthanide or transition metal may be ionized to +3 and have an ionic radius of 0.114 nm or less. The lanthanide or transition metal may include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or a combination thereof. The lanthanide or transition metal may be scandium, zinc, or cerium. The dopant may constitute 10 ppm to 6 wt. % based on the total weight of the powder mixture. The dopant may be 0.1 wt. % to 5 wt. % ceria based on the total weight of the powder mixture. The dopant may be less than 3 wt. % ceria based on the total weight of the powder mixture. The dopant compound may be ceria (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 7H 2 O), or cerium(III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O).

[0008] The step of ball milling the powder slurry may include containing the powder mixture, the solvent, and the alumina grinding media in a polymer-lined ball milling vessel. The solvent may be distilled water or deionized water (ethyl and isopropyl alcohol). An organic binder may be added to the powder slurry before spray drying the powder slurry. The organic binder may be water-soluble. The organic binder may be 3% to 9% by weight based on the total weight of the powder slurry. The composition after ball milling is stoichiometric 3Y 2 O 3 :5Al 2 O 3 (0.6:1) and less than 3 wt.% additional Al 2 O 3 Additional Al may be included. 2 O 3 may include eroded portions of the alumina grinding media.

[0009]

[0009] The step of consolidating the spray-dried powder may include uniaxial pressing or cold isostatic pressing. The step of consolidating the spray-dried powder may be performed at room temperature in air. The step of consolidating the spray-dried powder may be performed at a pressure of 500 psi to 1250 psi. The calcination may be performed at a temperature of 1100°C to 1650°C, or 1450°C to 1550°C. The calcination may be performed for a period of 2 hours to 64 hours, or 8 hours to 16 hours. The step of milling the YAG compact may include the compact and a solvent being contained in a polymer-coated milling vessel. The solvent may be ethanol alcohol or isopropyl alcohol. The step of milling the YAG compact may include milling for at least 6 hours. The step of milling the YAG compact may include the YAG compact material self-fracturing to produce a YAG powder having an average particle size distribution of less than 100 μm. The average particle size distribution may be less than 63 μm, or less than 44 μm. The milled YAG compacted material may be sieved prior to drying. The YAG powder may have a bimodal particle size distribution. Drying may be performed at a temperature of less than 90° C.

[0010] In some embodiments, a method of synthesizing a doped yttrium aluminum garnet (YAG) powder includes providing powders of yttria, silica, and at least one dopant formed of a lanthanide or transition metal oxide, hydrate, nitrate, or chloride, and mixing to form a powder mixture, where no alumina is added to the powder mixture. The method may further include ball milling the powder mixture in the presence of an alumina grinding medium and a solvent to form a powder slurry, adding an organic binder to the powder slurry and mixing to form a sprayable powder slurry, and spray drying the sprayable powder slurry to form a spray-dried powder. The method may further include compacting the spray-dried powder to 35% or less of theoretical density to form a powder compact. The method may further include firing the powder compact in air to 50% or less of theoretical density to form a YAG compact. The method may further include providing a yttrium aluminum garnet compact having at least 92% or more Y by weight. 3 Al 5 O 12 The method may further include milling the YAG compact without grinding media and then drying to produce the doped YAG powder.

[0011] In an embodiment, the yttrium aluminum garnet (YAG) composition comprises Y 3 Al 5 O 12 and less than 3 wt.% additional Al 2 O 3 and additional Al 2 O 3 comprises an eroded portion of the alumina grinding media. The composition may further comprise a dopant concentration of at least 1 atomic %. An article, such as a phosphor wheel, may comprise a yttrium aluminum garnet (YAG) composition as described above.

[0012] A further understanding of the nature and advantages of the disclosed technology may be realized by reference to the remaining portions of the specification and the drawings. [Brief description of the drawings]

[0013] [Figure 1] 1 is a flowchart of an exemplary method. [Diagram 2]

[0014] 1 is a graph illustrating the amount of alumina eroded as a function of the input weight ratio of alumina grinding media to yttria according to an exemplary method. [Diagram 3]

[0015] 1 is an x-ray diffraction plot of a YAG powder doped with ceria by an exemplary method. [Figure 4]

[0016] 1 is a scanning electron microscope (SEM) image of cerium doped YAG powder according to an exemplary method, for example, after sintering at 1500° C. in air for 8 hours. [Diagram 5]

[0017] 1 is an x-ray diffraction plot of undoped YAG powder after repeated firing cycles according to an exemplary method. [Figure 6]

[0018] 1 is a SEM image showing spot energy dispersive spectroscopy (EDS) analysis of various spots of a comparative cerium doped YAG powder after sintering at 1600° C. for 8 hours in air. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Introduction

[0019] As discussed above, the YAG powders produced using previous methods do not meet the demands of yield, cost and sinterability. Specifically, previous solid-state methods for producing YAG powder require repeated firing for longer periods and at higher temperatures, thus resulting in poor process efficiency, e.g., low production yields. Also, previous solid-state methods for producing YAG powder require higher sintering temperatures, e.g., 1600°C or higher, to achieve high density articles.

[0015]

[0020] Here, the inventors have discovered that by using alumina grinding media in the first (ball) milling, consolidating the resulting powder slurry before calcination, and using little or no grinding media in the final milling, a simpler and more efficient production process is achieved.

[0016]

[0021] Without being bound by theory, it is hypothesized that the disclosed method promotes more efficient conversion to the YAG phase during firing and also prevents the introduction of undesirable impurities during each milling process. It has been found that controlling the alumina content via ball milling with alumina grinding media results in a more efficient process, e.g., a process that provides a stoichiometric or superstoichiometric alumina content via milling, thereby improving the conversion to the YAG phase and avoiding the introduction of undesirable impurities. Consolidating the powder slurry prior to firing further improves the conversion to the YAG phase, which can advantageously be done at lower temperatures, for shorter periods, and / or with fewer firing cycles, all of which contribute to a more efficient process, e.g., a process with improved yields.

[0017]

[0022] Furthermore, by not introducing any grinding media in the post-calcination milling, the process provides higher purity and better control of the component composition, which results in a purer YAG powder, e.g., YAG powder with fewer impurities. Without being bound by theory, the combination of pre-calcination compaction in conjunction with the introduction of alumina via milling contributes to a more uniform dispersion of alumina within the yttria, which allows the reaction between alumina and yttria to be completed in a shorter period of time and / or at a lower temperature, which in turn enhances the phase conversion to YAG. Importantly, by using the disclosed method, the dopant concentration can be advantageously controlled. As a result, the doped YAG contains fewer undesirable impurities.

[0018]

[0023] The disclosed method also provides a YAG powder that performs better than conventional YAG powders. For example, the disclosed YAG powder exhibits high sinterability, e.g., the YAG powder sinters to higher densities at relatively low sintering temperatures than conventional solid synthesis powders. This is due to the use of lower sintering temperatures provided by using the milling and compaction steps described above. Because the YAG phase transformation is achieved at relatively low sintering temperatures, the disclosed YAG powder beneficially has fewer hard agglomerates and a smaller average particle size. In contrast, conventional YAG powders are prepared at higher sintering temperatures, which detrimentally form harder agglomerates resulting in poor sinterability. For example, during subsequent sintering, the disclosed YAG powder reaches 98% of theoretical density at 1537°C for 8 hours, while a commercially available YAG powder (Intematix G91, Fremont, CA) can only reach 83% of theoretical density at 1537°C for 8 hours. As a result, solid state processes are desirable to produce high quality powders that have controlled dopant concentrations, have high sinterability, and are more cost-effective to produce.

[0019]

[0024] The disclosed methods provide YAG suitable for a wide variety of applications, such as phosphor wheels, light emitting diodes (LEDs), including white light emitting diodes (WLEDs), NIR (near infrared) transmitting windows for optical lenses and laser-based vehicle engine ignition systems (e.g., as a spark plug replacement), lasers, laser guns, etc.

[0020] YAG powder synthesis method

[0025] The present disclosure relates to a method for synthesizing YAG powder having the above-mentioned advantages. An example of the method is shown in FIG. 1. The method includes mixing yttria and silica powders to form a powder mixture, and ball milling the powder mixture to form a powder slurry. Importantly, the ball milling is performed in the presence of an alumina grinding medium and a solvent. This is important because the amount of alumina to the powder slurry can be controlled, and even superstoichiometric amounts of alumina can be introduced if desired, but without the introduction of undesirable impurities from conventional grinding media, such as milling balls. The powder mixture is alumina-free in some cases (alumina is not added to the powder). The method further includes spray drying the powder slurry to form a spray-dried powder, and compacting the spray-dried powder to 35% or less of theoretical density to form a green compact. This advantageously allows the green compact to convert to the YAG phase more easily during firing than loose green materials. The method further includes sintering the compact in air to 50% or less of theoretical density to form a YAG compact, and milling the YAG compact without grinding media and then drying to produce a YAG powder. Milling the YAG compact without grinding media is important because it prevents undesirable impurities from being introduced into the final powder composition from the milling balls. Each of these steps is discussed in more detail below.

[0021]

[0026] As noted above, the use of the above-mentioned processes, for example ball milling (using aluminum grinding media), optionally in conjunction with a consolidation step, provides the surprising results described above.

[0022] initial powder

[0027] As described above and illustrated in FIG. 1, the method includes the steps of: 2 O 3 ) and silica (SiO 2 ) to form a powder mixture.

[0023]

[0028] The initial powder used in the mixing step includes yttria and silica. In some cases, the yttria powder is high purity yttria. For example, the yttria powder may have a purity of 2N (99%) or higher, such as 3N (99.9%) or 4N (99.99%). In some embodiments, the yttria powder has a purity of 3N. In some cases, the yttria powder has a purity of 3N or higher.

[0024]

[0029] Silica and yttria may be mixed as separate powders or the starting powder may be, for example, silica-enriched yttria. In such cases, no mixing step is necessary and a silica / yttria powder may simply be provided. In a preferred embodiment, the silica is fumed silica. Fumed silica, or pyrogenic silica, has a low bulk density and a high surface area. Such characteristics make fumed silica highly reactive in powder synthesis, especially during the high temperatures used in calcination. During calcination, silica reacts with yttria and alumina to form a Y-Al-Si-O liquid phase. This Y-Al-Si-O liquid phase evaporates at temperatures above 1350°C. By adding silica to form a liquid phase, a cleaning effect is achieved by the Y-Al-Si-O liquid phase evaporation. The transient liquid phase removed by evaporation during calcination (or sintering) can be a cleaning agent. Suitable yttria and silica powders are commercially available, for example, yttria (from Materion Corp.) and fumed silica (from Sigma-Aldrich).

[0025]

[0030] In some embodiments, the powder mixture comprises 0.005% to 2.0% by weight of silica and the balance yttria. For example, the powder mixture may comprise 0.005% to 2.0% by weight of silica, such as 0.01% to 1.5% by weight of silica, 0.01% to 1.0% by weight of silica, 0.01% to 0.5% by weight of silica, 0.05% to 0.4% by weight of silica, 0.1% to 0.4% by weight of silica, 0.1% to 0.3% by weight of silica, or 0.2% to 0.3% by weight of silica. In terms of the lower limit, the powder mixture may comprise more than 0.005% by weight of silica, such as more than 0.01% by weight, more than 0.05% by weight, more than 0.1% by weight, or more than 0.2% by weight of silica. In terms of upper limits, the powder mixture may contain less than 2.0 wt.% silica, such as less than 1.5 wt.%, less than 1.0 wt.%, less than 0.5 wt.%, less than 0.4 wt.%, or less than 0.3 wt.% silica. In some embodiments, the silica is included in an amount of 0.1 wt.% to 0.3 wt.% silica based on the total weight of the powder mixture. Examples herein include silica in an amount of 0.25 wt.% silica based on the total weight of the powder mixture.

[0026]

[0031] In some embodiments, the powder mixture comprises 93.0 wt% to 99.99 wt% yttria. The remaining yttria content of the powder mixture also depends on whether optional dopants are added, as discussed below. For example, the powder mixture may comprise 93.0 wt% to 99.99 wt% yttria, such as 93.0 wt% to 99.95 wt% yttria, 95.0 wt% to 99.9 wt% yttria, 97.0 wt% to 99.8 wt% yttria, or 98.0 wt% to 99.8 wt% yttria. In terms of lower limits, the powder mixture may comprise more than 93.0 wt% yttria, such as more than 95.0 wt%, more than 97.0 wt%, more than 98.0 wt%, more than 99.0 wt%, more than 99.5 wt%, or more than 99.9 wt% yttria. In terms of upper limits, the powder mixture may contain less than 99.99 wt% yttria, such as less than 99.95 wt%, less than 99.9 wt%, less than 99.8 wt%, less than 99.5 wt%, or less than 99.0 wt% yttria. In some embodiments, yttria is present in an amount of 99.7 wt% to 99.8 wt% based on the total weight of the powder mixture when no dopant is added. In some embodiments, yttria is present in an amount of 96.0 wt% to 99.0 wt% based on the total weight of the powder mixture when a dopant is added.

[0027]

[0032] In some cases, the powder mixture contains little, if any, alumina (Al 2 O 3 In some embodiments, the powder mixture comprises alumina (Al 2 O 3) or substantially free of yttria. In some cases, no alumina is added to the powder mixture. In some embodiments, the powder mixture includes zero (0.00 wt%) to 0.5 wt% alumina. For example, the powder mixture may include 0.01 wt% to 0.5 wt% alumina, such as 0.05 wt% to 0.4 wt% alumina, 0.1 wt% to 0.3 wt% alumina, or 0.1 wt% to 0.2 wt% alumina. With respect to the upper limit, the powder mixture may include less than 0.5 wt% alumina, such as less than 0.4 wt%, less than 0.3 wt%, or less than 0.2 wt% alumina. This is important because alumina as the initial powder can be eliminated from the process. It has been found that using alumina grinding media as the only source of alumina introduced during ball milling not only simplifies the process, but also allows the alumina to be uniformly distributed in the yttria and the amount of alumina relative to the powder slurry can be controlled during ball milling.

[0028]

[0033] Optionally, a dopant is included in the powder mixture. The dopant may be used in the form of a compound, and the dopant (dopant compound) may be added and / or contained in the powder mixture. In some embodiments, the powder mixture includes 10 ppm to 6.0 wt. % of the dopant, as well as the above-mentioned silica and the balance yttria. For example, the powder mixture may include 10 ppm to 6.0 wt. % of the dopant, such as 0.01 wt. % to 6.0 wt. % of the dopant, 0.5 wt. % to 5.0 wt. % of the dopant, 1.0 wt. % to 4.0 wt. % of the dopant, 1.5 wt. % to 3.5 wt. % of the dopant, 2.0 wt. % to 3.0 wt. % of the dopant, or 2.3 wt. % to 2.7 wt. % of the dopant. In terms of the lower limit, the powder mixture may contain more than 10 ppm of dopant, such as more than 0.01 wt%, more than 0.5 wt%, more than 1.0 wt%, more than 1.5 wt%, more than 2.0 wt%, or more than 2.3 wt% of dopant. In terms of the upper limit, the powder mixture may contain less than 6.0 wt%, such as less than 5.0 wt%, less than 4.0 wt%, less than 3.5 wt%, less than 3.0 wt%, or less than 2.7 wt% of dopant. In a preferred embodiment, the dopant is included in an amount of 2.0 wt% to 3.0 wt%, based on the total weight of the powder mixture.

[0029]

[0034] In some embodiments, the dopant is cerium, which is added in the form of ceria. For example, the powder mixture may contain 0.1 wt% to 5.0 wt% ceria, such as 0.5 wt% to 5.0 wt% ceria, 1.0 wt% to 4.0 wt% ceria, 1.5 wt% to 3.5 wt% ceria, 2.0 wt% to 3.0 wt% ceria, or 2.3 wt% to 2.7 wt% ceria. In terms of the lower limit, the powder mixture may contain more than 0.1 wt% ceria, such as more than 0.5 wt%, more than 1.0 wt%, more than 1.5 wt%, more than 2.0 wt%, or more than 2.3 wt% ceria. In terms of the upper limit, the powder mixture may contain less than 5.0 wt% ceria, such as less than 4.0 wt%, less than 3.5 wt%, less than 3.0 wt%, or less than 2.7 wt% ceria. In a preferred embodiment, ceria is included in an amount of 2.5% by weight ±10%, based on the total weight of the powder mixture.

[0030]

[0035] The average particle size of the initial powder is not limited. For example, the initial powder may range from an average particle size of 0.001 μm to 50 μm, such as 0.005 μm to 25 μm, 0.01 μm to 10 μm, or 0.01 μm to 5 μm. For the lower limit, the average particle size of the initial powder may be greater than 0.001 μm, such as greater than 0.005 μm, or greater than 0.01 μm. For the upper limit, the average particle size of the initial powder may be less than 50 μm, such as less than 25 μm, less than 10 μm, or less than 5 μm. The average particle size of the initial powder is not a dominant factor in predicting, for example, the density of the green compact formed and / or the completeness of the phase conversion to YAG after firing. More important to providing complete YAG phase conversion in the methods herein is the consolidation before firing, which is described in detail below.

[0031] First Milling

[0036] As described above, the method includes ball milling the powder mixture in the presence of an alumina grinding medium and a solvent to form a powder slurry. As used herein, "ball milling" refers to the first milling step of the method in which alumina is used as the grinding medium. The use of such alumina differs from the use of conventional milling balls, which may not contain alumina. This step is important because the alumina content can be controlled, which results in the provision of stoichiometric YAG or superstoichiometric alumina content that may enhance phase conversion to YAG if desired.

[0032]

[0037] Ball milling of the powder mixture may be carried out in the presence of alumina grinding media (and a solvent) to form a powder slurry. The inventors have found that during ball milling, alumina from the grinding media is eroded, advantageously providing a source of alumina for the powder slurry. Advantageously, no additional alumina needs to be added or present.

[0033]

[0038] Alumina grinding media are important because the amount of alumina eroded from the alumina grinding media can be beneficially controlled. As a result, the composition of the resulting YAG can also be controlled. This contributes to process efficiency, as well as the above-mentioned improved production yield and / or fewer firing cycles. Conventional YAG synthesis processes do not use alumina grinding media to purposely erode alumina and / or deviate from stoichiometric YAG, and therefore cannot achieve these benefits.

[0034]

[0039] Determinants of the amount of alumina provided to the powder slurry during ball milling include the milling energy, the milling speed in revolutions per minute (RPM), the diameter of the ball milling container, the powder mixture input to the powder slurry, the volume of the powder slurry, the volume and / or weight of the alumina grinding media, and the wear characteristics of the alumina grinding media. The factors may be interrelated, for example, the larger the diameter of the container, the slower it rotates. The peripheral speed of the mill is controlled to prevent a centrifuge-like effect in which the balls are retained in the peripheral portion of the mill rather than cascading down the container.

[0035]

[0040] Y 2 O 3 (Yttria) vs. Al 2 O 3 The nominal stoichiometric ratio by moles of (alumina) is 3:5 or 3Y 2 O 3 :5Al 2 O 3 In some cases, after ball milling, a superstoichiometric amount of alumina is present in the powder slurry. In other words, the ratio of yttria to alumina is 3:5 (0.6:1) or more, such as 3:5.1 (0.59:1), 3:5.2 (0.58:1), 3:5.3 (0.57:1), 3:5.35 (0.56:1), 3:5.4 (0.555:1), 3:5.5 (0.55:1), 3:5.6 (0.54:1), 3:5.7 (0.53:1), or more. In some embodiments, the composition of the powder mixture after ball milling is 3:5 (0.6:1) to 3:5.5 (0.55:1) Y:Alumina ratio. 2 O 3 :Al2 O 3 The ratio is:

[0036]

[0041] After ball milling, the composition was found to be stoichiometric 3Y 2 O 3 :5Al 2 O 3 and less than 3 wt. % additional Al based on the total weight of the powder components. 2 O 3 For example, additional Al 2 O 3 The amount of added Al ranges from zero (0.00) wt% to 3.0 wt%. 2 O 3 , for example 0.1 wt.% to 3.0 wt.% additional Al 2 O 3 , 0.5wt% to 2.5wt% additional Al 2 O 3 , or 1.0 wt.% to 2.0 wt.% additional Al 2 O 3 As for the lower limit, additional Al 2 O 3 is greater than zero (0.00) wt.% additional Al. 2 O 3 %, e.g., more than 0.1 wt. % additional Al 2 O 3 , more than 0.5 wt.% additional Al 2 O 3 %, or more than 1.0 wt.% additional Al 2 O 3 Regarding the upper limit, additional Al 2 O 3 The amount of additional Al is less than 3.0 wt.%. 2 O 3 , e.g. less than 2.5 wt. % additional Al 2 O 3 or less than 2.0 wt.% additional Al 2 O 3 Additional Al may be used. 2 O 3 includes eroded portions of the alumina grinding media. The eroded portions result from wear of the alumina grinding media during ball milling.

[0037]

[0042] The alumina grinding media is of high purity. In some embodiments, the alumina grinding media is 95.0% to 99.99% Al. 2 O 3 For example, alumina grinding media has a purity of 95.0% to 99.9% Al. 2 O 3 , e.g. 95.0%~99.8% Al 2 O 3 , 97.0%~99.8% Al 2 O 3 , 98.0%~99.8% Al 2 O 3 , 99.0%~99.8% Al 2 O 3 , or 99.5% to 99.8% Al 2 O 3 In terms of the lower limit, the alumina grinding media has a purity of greater than 95.0% Al. 2 O 3 , e.g., more than 95.0% Al 2 O 3 , over 96.0% Al 2 O 3 , over 97.0% Al 2 O 3 , over 98.0% Al 2 O 3 , over 99.0% Al 2 O 3 , over 99.5% Al 2 O 3 , over 99.8% Al 2 O 3 , or more than 99.9% Al 2 O 3 In terms of the upper limit, the alumina grinding media should have a purity of less than 100% Al. 2 O 3 , e.g., less than 99.99% Al 2 O 3 , less than 99.9% Al 2 O 3 , or less than 99.8% Al 2 O 3 In a preferred embodiment, the alumina grinding media has a purity of 95.0% to 99.8% Al. 2 O 3The high purity alumina grinding media has a purity of α-Al 2 O 3 The alumina grinding media has a diameter ranging from 3 mm to 25 mm. The alumina grinding media is wear resistant, with a Vickers hardness of 14 GPa (±10%) and a hardness of 3.88 g / cm 3 ~3.97g / cm 3 The abrasion of alumina grinding media produces Al with an average particle size distribution in the micron range, e.g., 1-10 μm. 2 O 3 The particles are applied to the powder mixture. 2 O 3 The particles are 1-5 μm or 1-3 μm. This is important because the conversion to the YAG phase during firing can be enhanced by controlling the amount of alumina present and by controlling the size of the alumina particles.

[0038]

[0043] In some cases, ball milling is performed in a polymer-coated ball milling vessel. The vessel diameter may range from 15 cm to 60 cm in diameter and 15 cm to 60 cm in height. Ball milling may be performed in a non-reactive vessel, such as a polyurethane-coated milling jar, such as an Abbethane jar with lifter unit manufactured by Paul O'Abbe (Bensenville, IL) having dimensions of (30 cm in diameter x 30 cm in height). The contents of the polymer-coated ball milling vessel include a powder slurry including a powder mixture, a solvent, and an alumina grinding media. The solvent may be distilled water or deionized water. The amount of solvent may range from 50 to 80% by weight based on the total weight of the powder mixture.

[0039]

[0044] Ball milling may be performed at a speed ranging from 15 RPM to 70 RPM. For example, the ball milling speed may be 15 RPM to 70 RPM, such as 30 RPM to 70 RPM, or 50 RPM to 70 RPM. Ball milling may be performed for a period of 1 hour to 64 hours. For example, the period of ball milling may be 1 hour to 64 hours, such as 4 hours to 48 hours, 8 hours to 24 hours, or 12 hours to 20 hours. In some embodiments, ball milling is performed at 60 RPM for 16 hours. The amount of alumina imparted to the powder slurry may be calculated by measuring the difference in weight of the alumina grinding media after ball milling relative to the initial weight of the alumina grinding media. The grinding media may be cylindrical or spherical or other shapes with dimensions of about 13 mm in diameter and / or height. For example, the grinding media may be 10 mm to 20 mm in diameter and 10 mm to 20 mm in height, e.g., 12 mm to 18 mm in diameter and 12 mm to 18 mm in height, or 13 mm to 16 mm in diameter and 13 mm to 16 mm in height. The wear (erosion by weight) of the alumina grinding media may be 5% to 10% by weight, e.g., 6% to 8% by weight, or 6.5% to 7% by weight.

[0040]

[0045] An organic binder may be added to the powder slurry before it is spray-dried. The organic binder is preferably water-soluble. Suitable organic binders include acrylic polymer-based ammonium solution (B-60A, commercially available from Rohm and Haas), or polyvinyl alcohol solution, and the like.

[0041]

[0046] The organic binder added prior to spray drying may be present in an amount ranging from 3 wt% to 9 wt% organic binder, e.g., 4 wt% to 8 wt% organic binder, 5 wt% to 7 wt% organic binder, or 5.5 wt% to 6.5 wt% organic binder based on the total weight of the powder slurry. In terms of the lower limit, the amount of organic binder added may be more than 3 wt% organic binder, e.g., more than 4 wt% organic binder, more than 5 wt% organic binder, or more than 5.5 wt% organic binder. In terms of the upper limit, the amount of organic binder added may be less than 9 wt% organic binder, e.g., less than 8 wt% organic binder, less than 7 wt% organic binder, or less than 6.5 wt% organic binder. In a preferred embodiment, the amount of organic binder added is 6 wt% ±10% based on the total weight of the powder mixture. The organic binder is then burned off during subsequent processing, e.g., during calcination, e.g., at 500° C. or higher.

[0042] spray drying

[0047] The method may further include spray drying the powder slurry to form a spray-dried powder. This step is important because spray drying forms discrete granules with a uniform distribution of yttria, silica, alumina, and optional dopants. Spray drying may be performed using a Yamato DL4120 (Santa Clara, CA) unit. The inlet temperature may range from 200°C to 400°C, e.g., 200°C to 350°C, 200°C to 300°C, 200°C to 280°C, 210°C to 270°C, 220°C to 260°C, or 230°C to 250°C. On the lower end, the inlet temperature may be greater than 200°C, e.g., greater than 210°C, greater than 220°C, or greater than 230°C. As regards the upper limit, the inlet temperature may be less than 400°C, for example less than 350°C, less than 300°C, less than 280°C, less than 270°C, less than 260°C, or less than 250°C. In a preferred embodiment, the inlet temperature is 240°C ± 10%. The outlet temperature may be in the range of 70°C to 110°C, for example 75°C to 105°C, 80°C to 100°C, or 85°C to 95°C. As regards the lower limit, the outlet temperature may be greater than 70°C, for example greater than 75°C, greater than 80°C, or greater than 85°C. As regards the upper limit, the outlet temperature may be less than 110°C, for example less than 105°C, less than 100°C, or less than 95°C. In a preferred embodiment, the outlet temperature is 85°C to 95°C. The spray drying is carried out under compressed air. The pressure for spray drying may be in the range of 0.01 MPa to 0.6 MPa compressed air, for example 0.02 MPa to 0.5 MPa, 0.05 MPa to 0.4 MPa, or 0.1 MPa to 0.3 MPa compressed air. In terms of the lower limit, the pressure may be greater than 0.01 MPa, for example greater than 0.02 MPa, greater than 0.05 MPa, or greater than 0.01 MPa. In terms of the upper limit, the pressure may be less than 0.6 MPa, for example less than 0.5 MPa, less than 0.4 MPa, or less than 0.3 MPa. In a preferred embodiment, the pressure is 0.1 to 0.3 MPa compressed air.

[0043]

[0048] The spray-dried powder comprises an average particle size distribution in the range of 0.1 μm to 425 μm. The average particle size distribution may be in the range of 0.1 μm to 425 μm, such as 0.1 μm to 300 μm, 0.1 μm to 200 μm, 0.1 μm to 100 μm, 0.1 μm to 75 μm, or 0.1 μm to 50 μm. In terms of the lower limit, the average particle size distribution may be greater than 0.1 μm, such as greater than 0.2 μm, greater than 0.3 μm, greater than 0.4 μm, or greater than 0.5 μm. In terms of the upper limit, the average particle size distribution may be less than 425 μm, such as less than 300 μm, less than 200 μm, less than 100 μm, less than 75 μm, or less than 50 μm. In an embodiment, the spray dried powder may be passed through a sieve (US mesh size No. 40, 425 μm) so that any grains 425 μm may be used for compaction.

[0044] Compaction

[0049] The method further includes a step of compacting the spray-dried powder to form a compact. Although the spray-dried powder is compacted, this provides several process advantages over conventional powder solid-state sintering processes that do not compact in this way. First, the compact has a higher green density compared to that of the loosely packed powder for sintering, and therefore the diffusion distance of the ions required to form the YAG phase is shorter, so the powder composition converts to the YAG phase more easily during subsequent sintering. Thus, during sintering, the formation of YAG proceeds at lower sintering temperatures and / or in shorter times than would be required for loosely packed powders. Furthermore, in some embodiments, the conversion to YAG is completed in a single sintering cycle. Second, by using a transient sintering aid, such as silica introduced into the initial powder mixture, a Y-Al-Si-O liquid phase forms during sintering. This also results in the formation of YAG proceeding more easily and at lower firing temperatures (and / or in shorter times or fewer firing cycles) due to the enhanced large scale conversion by the liquid YA-Si-O sintering aid. Thus, consolidation by the methods described herein is important for the formation of YAG, which requires fewer, if any, repeated firing cycles.

[0045]

[0050] Consolidation of the spray-dried powder is performed to reduce the powder interparticle distance to improve YAG formation during subsequent firing. Consolidating the spray-dried powder to form a compact may include consolidating to 35% or less of theoretical density. For example, consolidating the spray-dried powder to form a compact may include consolidating to 20% of theoretical density to 40% of theoretical density, such as 25% of theoretical density to 40% of theoretical density, 30% of theoretical density to 40% of theoretical density, or 35% of theoretical density to 40% of theoretical density. Consolidating the spray-dried powder to form a compact may include consolidating to 20% or less of theoretical density, 25% or less of theoretical density, 30% or less of theoretical density, 35% or less of theoretical density, or 40% or less of theoretical density. In a preferred embodiment, the amount of consolidation is 35%±10% or less of theoretical density. The density of the material consolidated to a target of 35% of the theoretical density is 1.593 g / cm 3 ±10%.

[0046]

[0051] The step of compacting the spray-dried powder may include uniaxial pressing or cold isostatic pressing. Compaction may be performed using a Hydramet unit. The pressure for compaction may range from 200 psi to 2000 psi, such as 300 psi to 1800 psi, 400 psi to 1600 psi, 500 psi to 1500 psi, or 1000 psi to 1500 psi. On the lower limit, the pressure may be greater than 200 psi, such as greater than 300 psi, greater than 400 psi, greater than 500 psi, or greater than 1000 psi. On the upper limit, the pressure may be less than 2000 psi, such as less than 1800 psi, less than 1600 psi, or less than 1500 psi. In a preferred embodiment, the pressure is between 500 psi and 1500 psi, such as between 1000 psi and 1500 psi.

[0047]

[0052] In some embodiments, consolidation involves forming the spray-dried powder (or granules) into a grinding media shape (0.75 inch diameter by 0.75 inch height) using a uniaxial press, such as a Hydramet uniaxial press. Although elevated temperatures are contemplated, consolidation of the spray-dried powder may be advantageously carried out at room temperature in air. Consolidation may include cold consolidation. The following are non-limiting exemplary pressures that may be suitable for consolidating spray-dried powders according to some embodiments herein: Consolidation of the spray-dried powder may be carried out at pressures of 500 psi to 1500 psi, e.g., 500 psi to 1250 psi, or 750 psi to 1000 psi.

[0048] Calcining

[0053] The method further includes sintering the green compact in air to 50% or less of theoretical density to form a YAG compact. 3 Al 5 O 12 In some embodiments, the 3Y 2 O 3 :5Al 2 O 3 At least 95%, or at least 97%, or at least 98%, or at least 99% of 3 Al 5 O 12 In some embodiments, 3Y 2 O 3 :5Al 2 O 3 100% of Y 3 Al 5 O 12 Firing further densifies the compact to a higher percentage of theoretical density compared to the powder compact, but the YAG compact remains in an unsintered state - in other words, the powder has not been compacted into a dense solid.

[0049]

[0054] For example, the step of firing the green compact to form a YAG compact may include firing to 50% or less of theoretical density. For example, the step of firing the green compact to form a YAG compact may include firing to 40% to 60% of theoretical density, such as 45% to 60% of theoretical density, or 45% to 55% of theoretical density. The step of firing the green compact to form a YAG compact may include firing to 40% or less of theoretical density, 45% or less of theoretical density, 50% or less of theoretical density, 55% or less of theoretical density, or 60% or less of theoretical density. In a preferred embodiment, the YAG compact is fired to 50% ± 10% or less of theoretical density. The density of the YAG compact fired to a target of 50% of theoretical density is 2.275 g / cm. 3 ±10%.

[0050]

[0055] Firing may be carried out in any suitable furnace, such as an Armil furnace, at a temperature in the range of 1100° C. to 1650° C. for a period in the range of 2 to 64 hours. Firing may be carried out in air.

[0051]

[0056] The temperature at which the firing is carried out ranges from 1100°C to 1650°C. For example, the firing is carried out at 1200°C to 1650°C, such as 1350°C to 1600°C, or 1450°C to 1550°C. As for the lower limit, the firing may be carried out at a temperature above 1100°C, such as above 1200°C, above 1350°C, or above 1450°C. As for the upper limit, the firing may be carried out at a temperature below 1650°C, such as below 1660°C, or below 1550°C. In a preferred embodiment, the firing is carried out at a temperature between 1450°C and 1550°C. Importantly, the firing is carried out in some embodiments at a temperature below what would traditionally be considered a sintering temperature, thereby avoiding sintering in some cases as described above. The disclosed method steps allow for firing at lower temperatures, without which the firing step would require higher temperatures and suffer from the associated problems and disadvantages.

[0052]

[0057] The calcination may be carried out at the above mentioned temperatures for a period ranging from 2 hours to 64 hours. For example, the calcination is carried out for 2 hours to 64 hours, such as 4 hours to 48 hours, 6 hours to 24 hours, or 8 hours to 16 hours, or 10 hours to 14 hours. In terms of the lower limit, the calcination may be carried out for a period of more than 2 hours, such as more than 4 hours, more than 6 hours, more than 8 hours, or more than 10 hours. In terms of the upper limit, the calcination may be carried out for a period of less than 64 hours, such as less than 48 hours, less than 24 hours, less than 16 hours, or less than 14 hours. In a preferred embodiment, the calcination is carried out for a period of 8 to 16 hours.

[0053]

[0058] Firing may be performed using a heat treatment schedule that includes one or more holds in a single firing cycle. Advantageously, firing in two (or more) temperature stages provides more complete conversion to the desired YAG phase. Each hold is associated with a temperature and a duration at that temperature. In some embodiments, firing includes a heat treatment schedule with one hold, two holds, three holds, four holds, or more holds. For example, firing may include a first hold at a first temperature for a first duration, a second hold at a second temperature for a second duration, optionally a third hold at a third temperature for a third duration, and optionally a fourth hold at a fourth temperature for a fourth duration.

[0054]

[0059] Thus, the firing may include at least two holding temperatures. The at least two holding temperatures at which the firing is performed may be in the range of 1100°C to 1650°C. For example, the at least two holding temperatures are in the range of 1200°C to 1650°C, such as 1350°C to 1600°C, or 1450°C to 1550°C. With respect to the lower limit, the at least two holding temperatures may be above 1100°C, such as above 1200°C, above 1350°C, or above 1450°C. With respect to the upper limit, the at least two holding temperatures may be below 1650°C, such as below 1660°C, or below 1550°C. In a preferred embodiment, the at least two holding temperatures are between 1450°C and 1550°C. The at least two holding temperatures may be the same or different.

[0055]

[0060] The calcination including at least two holding temperatures may be carried out at the above mentioned temperatures for a period ranging from 2 hours to 64 hours for each hold. For example, the at least two holding times may be in the range of 2 hours to 64 hours, such as 4 hours to 48 hours, 6 hours to 24 hours, or 8 hours to 16 hours, or 10 hours to 14 hours. In terms of the lower limit, the at least two holding times may be of a period of more than 2 hours, such as more than 4 hours, more than 6 hours, more than 8 hours, or more than 10 hours. In terms of the upper limit, the at least two holding times may be of a period of less than 64 hours, such as less than 48 hours, less than 24 hours, less than 16 hours, or less than 14 hours. In a preferred embodiment, the at least two holding times are of a period of 8 to 16 hours. The at least two holding times may be the same or different.

[0056]

[0061] In a preferred embodiment, the firing includes a first hold having a first temperature for a first period of time and a second hold having a second temperature for a second period of time, for example, the firing includes a first hold at a first temperature of 1450°C-1550°C for a first period of 8-16 hours and a first hold at a first temperature of 1450°C-1550°C for a first period of 8-16 hours. In one example, the firing is performed at a first temperature of 1525°C for a period of 8 hours and then at a second temperature of 1550°C for a period of 8 hours in a single cycle. Single cycle means continuous and without cooling between holds.

[0057]

[0062] Importantly, sintering affects the transformation of the previously green compact into a yttrium aluminum garnet (YAG) compact, the phase content of which may be determined by suitable techniques such as x-ray diffraction. YAG is herein defined as a YAG phase having a crystal structure within the cubic category. 3 Al 5 O 12 The phase content of the YAG compact is at least 90% by weight Y. 3 Al 5 O 12 , for example at least 91 wt. % Y 3 Al 5 O 12, at least 92% by weight of Y 3 Al 5 O 12 , at least 93% by weight of Y 3 Al 5 O 12 , at least 94% by weight of Y 3 Al 5 O 12 , at least 95% by weight of Y 3 Al 5 O 12 , at least 96% by weight of Y 3 Al 5 O 12 , at least 97% by weight of Y 3 Al 5 O 12 , at least 98% by weight of Y 3 Al 5 O 12 or at least 99% by weight of Y 3 Al 5 O 12 Includes.

[0058]

[0063] After firing, the phase content may advantageously include a small amount of secondary phases. The secondary phases may include silica, alumina, ceria (or other dopants), or phases YAM or YAP, which show incomplete phase conversion to YAG. The phase content of the YAG compact includes up to 10% by weight of secondary phases, such as up to 9% by weight of secondary phases, up to 8% by weight of secondary phases, up to 7% by weight of secondary phases, up to 6% by weight of secondary phases, up to 5% by weight of secondary phases, up to 4% by weight of secondary phases, up to 3% by weight of secondary phases, up to 2% by weight of secondary phases, up to 1% by weight of secondary phases. In some embodiments, zero or substantially zero secondary phases are present and / or detectable.

[0059]

[0064] An additional hold for binder burnout may precede the firing or may be included in the firing heat treatment schedule. This hold is typically at a temperature lower than the hold temperature for the firing to achieve phase conversion to YAG. The binder burnout may be performed as part of the heat ramp to the firing temperature as detailed above. The temperature at which the binder burnout is performed ranges from 400°C to 600°C. For example, the binder burnout is performed at 400°C to 600°C, such as 425°C to 575°C, or 450°C to 550°C, or 475°C to 525°C. In terms of the lower limit, the binder burnout may be performed at a temperature above 400°C, such as above 425°C, above 450°C, or above 475°C. In terms of the upper limit, the binder burnout may be performed at a temperature below 600°C, such as below 575°C, below 550°C, or below 525°C. In a preferred embodiment, the binder combustion is carried out at a temperature of about 500° C.±10%.

[0060]

[0065] Optionally, the firing may be repeated. In preferred embodiments, only a single firing is performed to provide conversion to YAG. In some embodiments, the firing is repeated once, and in other embodiments, twice. The method may include a total of one, two, or three firings. In some embodiments, the firing is repeated at most once. The method does not include more than three firings. In embodiments where the firing is repeated, silica is added before each subsequent firing. In the case of repeated firing, the repeated cycle may include any or all of the steps of adding silica, ball milling, spray drying, and compacting during each repeated cycle.

[0061] Second Milling (After Firing)

[0066] The method may further include milling the YAG compact, followed by drying the milled compact to produce YAG powder. The inventors have discovered that the milling may be performed in the absence of any added grinding media or grinding balls. Beneficially, no grinding media is required or added, since the YAG compact material itself serves as the grinding media, i.e., the milling is self-generating. In some embodiments, the YAG compact comprises a plurality of compacts, such as those formed into a grinding media shape (0.75 inches diameter by 0.75 inches height) using uniaxial pressing, as in the cold compaction step described above. This step of using the YAG compact to self-mill is important, as it ensures that no impurities are introduced during milling. Thus, a common source of additional contamination from impurities, such as those from the grinding media, is advantageously eliminated.

[0062]

[0067] The milling may be carried out in a polymer-coated milling vessel. In some cases, for vessels used in ball milling as previously described, the diameter of the vessel may range from 15 cm to 60 cm in diameter and 15 cm to 60 cm in height. The milling may be carried out in a non-reactive vessel, such as a polyurethane-coated milling jar, such as an Abbethane jar with lifter unit manufactured by Paul O'Abbe (Bensenville, IL) having dimensions of (30 cm in diameter x 30 cm in height). The contents of the polymer-coated milling vessel include the YAG compact and a solvent. The vessel is free or substantially free of additional grinding media. The step of milling the YAG compact includes the YAG compact material self-fracturing to produce the YAG powder. The solvent may be ethanol alcohol or isopropyl alcohol. The amount of solvent ranges from 50 to 80% by weight based on the total weight of the YAG solid constituents.

[0063]

[0068] Milling of the YAG may be performed at a speed ranging from 15 RPM to 70 RPM. For example, the milling speed may be from 15 RPM to 70 RPM, such as from 30 RPM to 70 RPM, or from 50 RPM to 70 RPM. Milling may be performed for a period of from 1 hour to 64 hours. For example, the period of milling may be from 1 hour to 64 hours, such as from 4 hours to 48 hours, from 8 hours to 24 hours, or from 12 hours to 20 hours. In some embodiments, milling is performed at 60 RPM for 16 hours. In a preferred embodiment, milling of the YAG compact is performed for a period of at least 6 hours.

[0064]

[0069] Milling the YAG compact produces a powder having an average particle size distribution of less than 100 μm. In some embodiments, the average particle size distribution is less than 63 μm, which corresponds to a powder passing through a 230 mesh sieve. In other embodiments, the average particle size distribution is less than 44 μm, which corresponds to a powder passing through a 325 mesh sieve. The milled YAG compact material is sieved before drying to remove any agglomerates. In some embodiments, the YAG powder has a bimodal particle size distribution. The milled YAG compact is then dried to produce the YAG powder.

[0065] Drying

[0070] Drying may be carried out in a suitable dryer, such as a Fisher Scientific Lab drying oven, at a temperature up to 90° C. In some embodiments, drying is carried out at a temperature below 90° C. Drying may be carried out for a period of 2 hours to 24 hours.

[0066]

[0071] The resulting YAG powder is 3 Al 5 O 12and in some embodiments, has a dopant concentration of 0.1 wt% to 3.0 wt%. The concentration of the initially introduced dopant is maintained at about ±10% during the process. In some embodiments, the concentration of the dopant is unchanged throughout the process steps. In aspects, the YAG powder can have up to 3 vol% oxides at the YAG grain boundaries as determined by x-ray diffraction (XRD) analysis. The oxides can include, for example, alumina or ceria. In some embodiments, less than 1 vol% oxides are present at the YAG grain boundaries. Although oxides present at the grain boundaries can make the YAG powder less suitable for certain applications requiring transparency, such powders can be useful for applications requiring translucency or where the presence of some oxides at the grain boundaries can be tolerated and even advantageous. For example, excess alumina at the YAG grain boundaries can result in increased thermal properties of the final product, such as increased thermal diffusivity. Superstoichiometric amounts of alumina, such as 2.1 wt% Al 2 O 3 So, the thermal diffusivity of YAG is 3.00mm 2 / sec to 3.11mm 2 / sec for a huge 4% improvement.

[0067]

[0072] The YAG powder obtained by the methods herein can then be fabricated into a final product, which may include sintering to achieve a high density product. Sintering by methods known in the art includes solid sintering, hot pressing, hot isostatic pressing, etc. Sintering of YAG requires temperatures between 1500°C and 1800°C.

[0068]

[0073] The temperature at which sintering is carried out is typically higher than the firing temperature of the processes herein. For example, sintering is carried out at 1500°C to 1800°C, such as 1525°C to 1775°C, or 1550°C to 1750°C. In terms of the lower limit, sintering may be carried out at a temperature above 1500°C, such as above 1525°C, above 1550°C, or above 1575°C. In terms of the upper limit, sintering may be carried out at a temperature below 1800°C, such as below 1775°C, or below 1750°C.

[0069]

[0074] Sintering may be carried out at the above mentioned temperatures for a period ranging from 2 hours to 64 hours. For example, sintering is carried out for 2 hours to 64 hours, such as 4 hours to 48 hours, 6 hours to 24 hours, or 8 hours to 16 hours, or 10 hours to 14 hours. In terms of the lower limit, sintering may be carried out for a period of more than 2 hours, such as more than 4 hours, more than 6 hours, more than 8 hours, or more than 10 hours. In terms of the upper limit, sintering may be carried out for a period of less than 64 hours, such as less than 48 hours, less than 24 hours, less than 16 hours, or less than 14 hours. In a preferred embodiment, sintering is carried out for a period of 8 to 16 hours.

[0070] YAG Structure and Composition

[0075] The present disclosure relates to yttrium aluminum garnet (YAG) powder synthesis. 2 O 3 (Yttria) vs. Al 2 O 3 (Alumina) stoichiometric 3:5 ratio or 3Y 2 O 3 :5Al 2 O 3 The standard formula Y corresponds to 3 Al 5 O 12 or a ratio of 0.6:1 Y 2 O 3 Against Al 2 O 3 The YAG crystal structure is a complex cubic structure containing three different oxygen polyhedra, and Y +3 ions occupy dodecahedral sites, and Al 3+ The ions occupy the octahedral and tetrahedral sites in a ratio of 2:3. This arrangement is due to the ionic radius:O -2 (1.4Å), Y +3 (1.281Å), Al 3+ (0.51 Å). The unit cell parameters can be changed from cubic symmetry by substitution with cations of different ionic radii. Cations with similar ionic radii are, for example, Ce. +3 Similarly to doping YAG by cation substitution with +3can be substituted. Cerium doped YAG, or Ce:YAG, is useful as a phosphor in cathode ray tubes, white light emitting diodes, and scintillators. Other dopants are also contemplated. The phosphors can be activated with, for example, transition metals or lanthanides.

[0071]

[0076] Advantageously, in addition to being easily tunable to a desired dopant, the YAG powder formed according to the processes herein may be easily sintered into a high density final article. For example, after subsequent sintering, the disclosed YAG powder forms an article that may reach 98% of theoretical density with 8 hours of sintering at 1537°C, while a commercially available YAG powder (Intematix G91, Fremont, CA) may reach only 83% of theoretical density with 8 hours of sintering at 1537°C. In some embodiments, the sintered YAG article may be 90% of theoretical density to 100% of theoretical density, such as 92% of theoretical density to 100% of theoretical density, or 94% of theoretical density to 99% of theoretical density. The step of sintering to form the YAG article may include sintering to 90% or more of theoretical density, 92% or more of theoretical density, 94% or more of theoretical density, 96% or more of theoretical density, or 97% or more of theoretical density. In a preferred embodiment, the YAG compact is sintered to 98%±10% or less of theoretical density.

[0072] Doped YAG

[0077] The YAG powder synthesis as disclosed herein may further include using a dopant including a lanthanide or transition metal prior to converting the initial yttria and silica to YAG. Suitable dopants include lanthanides or transition metals ionized to +3. Suitable dopants may include those having an ionic radius of 0.114 nm or less. The dopant is introduced into the process with the initial yttria, silica, and / or silica-enriched yttria powder. The dopant may be enriched within the yttria powder or introduced as a separate powder that is mixed prior to creating the powder slurry.

[0073]

[0078] Lanthanides include chemical elements having atomic numbers 57-71 and are characterized as having one valence electron in the 5d shell. Suitable lanthanides include lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium. In general, transition metals are elements whose atoms have partially filled d subshells or can give rise to cations with incomplete d subshells. For purposes of this specification, scandium and zinc are considered transition metals. Suitable transition metals include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium. Lanthanides or transition metals as dopants herein may include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or combinations thereof. In some embodiments, the dopant is scandium, zinc, or cerium.

[0074]

[0079] The dopants introduced during YAG powder synthesis as disclosed herein may be in the form of a compound. The compound may be an oxide, hydrate, nitrate, chloride, or combinations thereof. Exemplary compounds for introducing cerium as a dopant include, but are not limited to, ceria (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 7H 2 O), cerium(III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2Exemplary compounds for introducing scandium as a dopant include, but are not limited to, scandium oxide (ScO). 2 O 3 ) and scandium chloride hexahydrate (ScCl 3 6H 2 Exemplary compounds for introducing zinc as a dopant include, but are not limited to, zinc oxide (ZnO) and zinc chloride (ZnCl 2 ).

[0075]

[0080] A more complete understanding of the components, methods and apparatus disclosed herein can be obtained by reference to the accompanying drawings, which are merely schematic representations based on convenience and ease of illustrating the disclosure, and are therefore not intended to illustrate relative sizes and dimensions of the devices or their components and / or to define or limit the scope of the example embodiments.

[0076]

[0081] FIG. 1 shows a flow chart of a method 100 according to an exemplary embodiment. Step 110 is the introduction of an initial powder. The initial powder may include yttria, silica, and an optional dopant (or dopant compound). The powders may be introduced (e.g., silica-enriched yttria) or may be introduced as separate powders that are mixed to form a powder mixture (e.g., yttria and fumed silica). The powder mixture may be free of alumina, e.g., the powder mixture does not include alumina. Step 120 includes milling the powder mixture. The ball milling in step 120 includes rotating a container containing the powder mixture of step 110 with a solvent and alumina grinding media. Alumina is introduced into the powder slurry due to the attrition of the alumina grinding media during milling 120, which is controlled via various parameters as discussed above. After the desired amount of alumina is incorporated into the powder slurry, an optional organic binder is added and the powder slurry is spray-dried 130 to produce discrete, uniformly distributed particles of alumina, yttria, silica, and optional dopants. The method 100 further includes a compacting step 140. The compacting is performed to achieve 35% or less of the theoretical density. This step is important to reduce the distance between ions in the compact. Thus, during the subsequent firing step 150, the conversion of the alumina, yttria, and silica phases (and optional dopants) of the compact to the YAG phase is more easily achieved to form a YAG compact. The more easily achieved phase conversion may be equal to at least one of the following, compared to the firing of loose materials: the firing may be performed at a lower temperature, for a shorter period of time, and / or in fewer cycles. The method 100 includes a step 160 of milling the YAG compact in the absence of grinding media, using the YAG material to collide and grind with itself to form milled YAG, which is then subjected to a step 170 of drying and optional sieving to produce YAG powder.

[0077]

[0082] In some embodiments, any or some of the steps or components disclosed herein may be considered optional. In some cases, any or some of the items described above herein may be expressly excluded, for example, by claim language. For example, claim language may be modified to state that the powder mixture does not include or excludes a particular oxide or dopant.

[0078]

[0083] As used herein, the limits "greater than" and "less than" may also include their associated numerical values. In other words, "greater than" and "less than" may be interpreted as "greater than or equal to" and "less than or equal to." It is contemplated that this language may be later amended in the claims to include "or equal to." For example, "greater than 4.0" may be interpreted as "greater than or equal to 4.0" and may also be later amended in the claims. EXAMPLES

[0079]

[0084] Example 1

[0085] Cerium-doped YAG (Ce:YAG) powder was prepared by mixing 2.58 wt.% CeO 2 The dopant concentration was 1000 ppm.

[0080]

[0086] 71.33 g of yttria (99.9% purity, Y-104, Materion), 0.313 g of fumed silica (Sigma-Aldrich), and 3.225 g of ceria (99.9% purity, C-1064, Materion) were introduced as a batch into an Abbethane (Paul O'Abbe) 1.6 gallon polyurethane lined milling jar to form a powder mixture. 756.4 g of alumina grinding media (97.7% purity, diameter approximately 13 mm x height approximately 13 mm) and 300 ml of deionized water were also added to the milling jar to form a powder slurry. The weight percentage of silica in Example 1 was 0.25 wt% based on the total weight of the powder mixture. The powder slurry was then ball milled at 60 RPM for 16 hours.

[0081]

[0087] After ball milling, the powder slurry was sieved using a polyethylene sieve (mesh #230) to separate the alumina grinding media and coarse particles from the powder slurry. The alumina grinding media was dried in a drying oven and reweighed. The weight of the alumina grinding media after ball milling was 700.1 g, and the amount of alumina eroded from the grinding media was calculated to be 56.3 g. Plot 200 in FIG. 2 shows the amount of alumina eroded from the alumina grinding media during ball milling, while the amount of alumina eroded from the grinding media is shown as a function of the input weight ratio of alumina grinding media to yttria. Without considering the amounts of dopant and fumed silica, the yttria and alumina constituents in the powder slurry were 3Y 2 O 3 :5Al 2 O 3 stoichiometric YAG (71.33 g yttria and 53.67 g alumina) and an additional 2.63 g alumina. The ratio of yttria to alumina (Y 2 O 3 :Al 2 O 3 The molar ratio of 3 to 5.25 (0.57:1) was calculated.

[0082]

[0088] The powder slurry further contained 8 g of an acrylic polymer-based binder (B-60A, Rohm and Hass), which was stirred into the powder slurry for 30 minutes using a magnetic bar and magnetic stirrer. The powder slurry was then spray dried using a Yamato DL410 spray dryer at an inlet temperature of 240° C., an outlet temperature of 90° C., and an air pressure of 0.1 MPa. The spray-dried powder slurry was passed through a 325 mesh polyethylene sieve to form a granulated powder for compaction.

[0083]

[0089] The granulated powder was then consolidated into a green compact which was then pressed into a grinding media shape (0.75 inch diameter x 0.75 inch height) using Hydramet uniaxial pressing. The green density was 1.49 g / cm 3, or equivalent to 32.7% of the theoretical density of YAG.

[0084]

[0090] Firing was carried out using the following heat treatment schedule: in a single cycle, heating to a temperature of 500°C and holding for 1 hour to remove the organic binder (binder burn-out hold), increasing the temperature to 1525°C and holding for 8 hours for firing, and then increasing the temperature to 1550°C and holding for 8 hours for further firing. The density of the fired compact was 2.21 g / cm 3 , or equivalent to 48.6% of the theoretical density of YAG. All debinding and sintering of the compacts was carried out in an air atmosphere.

[0085]

[0091] The calcined compact in 300 ml of ethanol was milled at 60 RPM for 6 hours and then sieved through a 230 mesh polyethylene sieve. The milled slurry was dried overnight (>12 hours) in a drying oven at a temperature of 90° C. After drying, the YAG powder was passed through a 325 mesh polyethylene sieve.

[0086]

[0092] FIG. 3 shows the x-ray diffraction pattern of the resulting YAG powder of Example 1. Plot 300 shows that the major phase is YAG with a peak designated "Y". The minor phase detected, as indicated by the peaks of lower intensity, is YAG with a peak designated "M". 4 Al 2 O 9 (YAM), YAlO with a peak indicated by "P" 3 (YAP), ceria with a peak designated "C", and alumina with a peak designated "A". This advantageously has a high YAG content compared to YAG formed from a conventional solid-state sintering process. The YAG phase content is about 92% by weight YAG. 3 Al 5 O 12 It was estimated that.

[0087]

[0093] To evaluate the sinterability of the synthesized YAG, the YAG powder was then mixed with 0.25 wt% fumed silica, consolidated by uniaxial pressing, and then sintered at 1500 °C in air for 8 h to produce a sintered dense compact (as shown in Figure 4 ).

[0088]

[0094] Figure 4 shows the results of the 2.58 wt% CeO2 sintering at 1500 °C for 8 h in air. 2 FIG. 4 is a scanning electron microscope (SEM) image 400 showing a typical microstructure of the YAG powder synthesized as in Example 1, with a dopant concentration of 1.0 g / cm. The composition of the powder is stoichiometric YAG and an additional 2.13 wt. % alumina (not accounting for cerium oxide). The sintered high density YAG ceramic has a mass of 4.41 g / cm. 3 400, which is equal to 97% of the theoretical density. As shown in image 400, the sintered YAG 400 includes YAG grains 410 with submicron spherical CeO at some grain boundaries. 2 grains 420. Advantageously, no alumina grains are present in image 400.

[0089]

[0095] Example 2

[0096] Undoped YAG (YAG) powder was synthesized. The batch contained 71.33 g of yttria (99.9%, Y-104, Materion) and 0.31 g of fumed silica (Sigma-Aldrich) as in Example 1, but without CeO 2 No yttria was added. The weight percent of silica in Example 2 was 0.25 wt% based on the total weight of the powder mixture. This powder was synthesized with a target of a 0.25 wt% superalumina YAG composition. The ratio of yttria to alumina (Y 2 O 3 :Al 2 O 3The molar ratio of CeO to YAG was calculated to be 3 to 5 (0.6:1). The heat treatment schedule for the compact was as follows: heat to a temperature of 500°C, hold for 1 hour to remove the organic binder, increase to a temperature of 1525°C, hold for 8 hours, sinter, then increase to a temperature of 1550°C and further sinter for 8 hours. All heat treatments were performed in air. The density of the sintered compact was approximately 50% of the theoretical density of YAG. The XRD plot (not shown) after heat treatment for Example 2 was similar to that in FIG. 3, except that the CeO 2 No peaks of any of the phases were observed. Intermediate phases YAP and YAM were observed. Alumina was not detected as a secondary phase.

[0090]

[0097] The resulting powder of Example 2 was then re-fired by repeating the firing heat treatment schedule of 1525° C. for 8 hours, followed by an increase in temperature to 1550° C. for 8 hours for a second cycle. Firing in the second cycle did not significantly affect the density of the compact, which was about 50% of the theoretical density of YAG after the second firing cycle.

[0091]

[0098] Any intermediate phases (YAP and YAM) were then converted to pure YAG, as shown in Figure 5, which shows the x-ray diffraction pattern of the resulting YAG powder of Example 2 after two firing cycles. Thus, the re-fired Example 2 shows the presence of only the YAG phase (no secondary phases are present), indicating complete phase conversion to YAG.

[0092]

[0099] Comparative example A

[0100] Cerium-doped YAG (Ce:YAG) powder was prepared by adding 3.0 wt.% CeO 2 The powder was prepared by in situ sintering of a conventional commercial yttria and alumina powder mixture with a dopant concentration of 0.01 g / cm. The composition of the powder was stoichiometric YAG and an additional 12 wt. % alumina (not accounting for cerium oxide). Figure 6 shows a density of 4.43 g / cm, which is equal to 97% of the theoretical density. 3FIG. 6 is an SEM image 600 showing spot energy dispersive spectroscopy (EDS) analysis of various spots of the YAG powder of Comparative Example A after sintering at 1600° C. for 8 hours in air, which resulted in a density of 1.0 μm. Importantly, this comparative sample required a significantly higher sintering temperature to achieve the same density as Example 1. Additionally, Comparative Example A contained a high content of alumina as a secondary phase, which is undesirable as it affects the purity and transmission properties of the YAG article. The secondary phases included alumina and ceria in amounts of about 12 wt % and 3 wt %, respectively.

[0093]

[0101] EDS analysis results were collected at five locations, as shown in Figure 6. Table 1 summarizes the EDS results for Comparative Example A. Based on the EDS analysis, YAG 610, ceria 620 and alumina 630 phases were identified. Thus, Comparative Example A contains an alumina phase as a minor oxide phase, while Example 1 and (refired) Example 2 do not.

[0094] [Table 1]

[0095]

[0102] Examples 3 and 4, Comparative Examples B and C

[0103] To compare the effect of different calcination heat treatments (varying by temperature and / or duration and / or number of cycles) on the phases produced, an expanded (target 375 g) batch of undoped powder as prepared in Example 2 was synthesized starting with 214 g yttria and 0.938 g fumed silica. As in Examples 1 and 2, the weight percentage of silica for the expanded batch was 0.25 wt% based on the total weight of the powder mixture. Alumina was introduced as in Examples 1 and 2 via attrition of the alumina grinding media during milling. This powder was synthesized targeting a stoichiometric YAG composition with 1.1 wt% excess alumina. The ratio of yttria to alumina (YAG) in the powder slurry was 0.25 wt%. 2 O 3 :Al 2 O 3The molar ratio of 3 to 5.13 (0.58:1) was calculated.

[0096]

[0104] Examples 3-4 and Comparative Examples B and C were compacted into powder compacts. The average densities before and after sintering (average density of at least five sample compacts per example, as a percentage of theoretical density) are shown in Table 2.

[0097]

[0105] All compacts were heated to a temperature of 500° C. and held for 1 hour for binder burnout, in other words for removal of the organic binder.

[0098]

[0106] Next, Examples 3-4 and Comparative Examples B and C were fired under the following different heat treatment conditions. Firing cycle for Example 3 - In a single cycle, the temperature was increased to 1525°C and held for 8 hours for firing, then increased to 1550°C and held for 8 hours for further firing. Firing cycle for Comparative Example B - fired in air, ramped to 1475°C and held for 8 hours. Firing Cycle for Comparative Example C - Temperature ramped to 1525°C and held for 8 hours and fired in air. Example 4 included a compact that was heat treated according to Comparative Example C (with the firing cycle as described above) and then fired at 1550° C. in an additional firing cycle of firing in air and held for 8 hours.

[0099]

[0107] The phases present as determined by x-ray diffraction analysis were compared for Example 3, Example 4, and Comparative Examples B and C. Table 2 also includes data for refired Example 2. Refired Example 2 was subjected to two cycles of sintering heat treatment, each cycle including 8 hours at 1525°C and 8 hours at 1550°C. The XRD data is summarized in Table 2 in terms of the content of YAG and other phases (if present). The other phases may include, for example, YAP, YAM, and alumina. The phases present for Example 3 were estimated. The relative density after sintering heat treatment (average of at least five sample compacts per example as a percentage of theoretical density) is also summarized in Table 2. For Example 4, which was already synthesized in powder form, the relative density is not applicable.

[0100] [Table 2]

[0108] The purest YAG powder (YAG with no detectable secondary phase) was obtained by calcination according to Example 2. 3 Al 5 O 12 Example 4, which included a first firing cycle at 1525° C. for 8 hours and a second firing cycle at 1550° C. for 8 hours, also yielded at least 94 wt. % Y. 3 Al 5 O 12 Firing according to Example 3 at 1525°C / 8h + 1550°C / 8h in a single firing cycle results in a high YAG conversion with a phase content of 92 wt.%. 3 Al 5 O 12 This results in high YAG conversion with a phase content of 0.1 to 0.5.

[0101]

[0109] Comparative Examples B and C showed unacceptable amounts of non-YAG phases, suggesting that the conversion to YAG was not yet complete. Comparative Example B contained only about 65 wt. % YAG. 3 Al 5 O 12Comparative Example C, which has a higher firing temperature than Comparative Example B, has only about 75 wt. % Y 3 Al 5 O 12 The phase contents were shown.

[0102] Embodiment

[0110] The following embodiments are contemplated: All combinations of features and embodiments are contemplated.

[0103]

[0111] Embodiment 1: A method of synthesizing a yttrium aluminum garnet (YAG) powder, comprising: introducing powders of yttria and silica to form a powder mixture, where no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media and a solvent to form a powder slurry; spray drying the powder slurry to form a spray-dried powder; consolidating the spray-dried powder to 35% or less of theoretical density to form a powder compact; firing the powder compact in air to 50% or less of theoretical density to form a YAG compact; and milling the YAG compact without grinding media and then drying to produce a YAG powder.

[0104]

[0112]

[0023] Embodiment 2: The method of any of the preceding or following embodiments, wherein the mixed powder further comprises a dopant comprising a lanthanide or a transition metal.

[0105]

[0113] Embodiment 3: The method of any of the preceding or following embodiments, wherein the lanthanide or transition metal is in the form of a compound, and the compound is an oxide, hydrate, nitrate, chloride, or combination thereof.

[0106]

[0114] Embodiment 4: The method of any of the preceding or following embodiments, wherein the lanthanide or transition metal is ionized to +3 and has an ionic radius of 0.114 nm or less.

[0107]

[0115] Embodiment 5: The method of any of the preceding or following embodiments, wherein the lanthanide or transition metal comprises scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or combinations thereof.

[0108]

[0116] Embodiment 6: The method of any of the preceding or following embodiments, wherein the lanthanide or transition metal is scandium, zinc, or cerium.

[0109]

[0117] Embodiment 7: The method of any of the preceding or following embodiments, wherein the dopant comprises 10 ppm to 6 wt. %, based on the total weight of the powder mixture.

[0110]

[0118] Embodiment 8: The method of any of the previous or following embodiments, wherein the dopant is 0.1% to 5% by weight of ceria, based on the total weight of the powder mixture.

[0111]

[0119] Embodiment 9: The method of any of the previous or following embodiments, wherein the dopant is less than 3 wt. % ceria, based on the total weight of the powder mixture.

[0112]

[0120] Embodiment 10: The compound is ceria (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 7H 2 O), or cerium(III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O).

[0113]

[0121] Embodiment 11: The method of any of the preceding or following embodiments, wherein the yttria powder has a purity of 2N or greater.

[0114]

[0122] Embodiment 12: The method of any of the preceding or following embodiments, wherein the yttria powder has a purity of 3N or greater.

[0115]

[0123] Embodiment 13: The method of any of the preceding or following embodiments, wherein the silica is 0.2% to 0.3% by weight, based on the total weight of the powder mixture.

[0116]

[0124] Embodiment 14: The method of any of the preceding or following embodiments, wherein the silica is fumed silica.

[0117]

[0125] Embodiment 15: The alumina grinding media is 95.0-99.8% Al 2 O 3 The method of any of the preceding or following embodiments, wherein the purity is

[0118]

[0126] Embodiment 16: The method of any of the preceding or following embodiments, wherein the step of ball milling the powder slurry includes containing the powder mixture, the solvent, and the alumina grinding media in a polymer-coated ball milling vessel.

[0119]

[0127] Embodiment 17: The method of any of the preceding or following embodiments, wherein the solvent is distilled or deionized water.

[0120]

[0128] Embodiment 18: The method of any of the preceding or following embodiments, further comprising adding and mixing an organic binder to the powder slurry prior to spray drying the powder slurry.

[0121]

[0129] Embodiment 19: The method of any of the preceding or following embodiments, wherein the organic binder is water-soluble.

[0122]

[0130] Embodiment 20: The method of any of the previous or subsequent embodiments, wherein the organic binder is 3% to 9% by weight, based on the total weight of the powder slurry.

[0123]

[0131] Embodiment 21: The composition after ball milling is stoichiometric 3Y 2 O 3 :5Al 2 O 3 (0.6:1) and less than 3 wt.% additional Al 2 O 3 36. The method of any of the preceding or following embodiments, comprising:

[0124]

[0132] Embodiment 22: Additional Al 2 O 3 The method of any of the preceding or following embodiments, wherein the alumina grinding media comprises an eroded portion of the alumina grinding media.

[0125]

[0133] Embodiment 23: The method of any of the preceding or following embodiments, wherein the step of consolidating the spray-dried powder comprises uniaxial pressing or cold isostatic pressing.

[0126]

[0134] Embodiment 24: The method of any of the previous or subsequent embodiments, wherein the step of compacting the spray-dried powder is performed at room temperature in air.

[0127]

[0135] Embodiment 25: The method of any of the previous or subsequent embodiments, wherein the step of compacting the spray-dried powder is carried out at a pressure of from 500 psi to 1250 psi.

[0128]

[0136] Embodiment 26: The method of any of the preceding or following embodiments, wherein the firing step is carried out at a temperature between 1100° C. and 1650° C.

[0129]

[0137] Embodiment 27: The method of any of the preceding or following embodiments, wherein the firing step is carried out at a temperature between 1450° C. and 1550° C.

[0130]

[0138] Embodiment 28: The method of any of the previous or following embodiments, wherein the calcining step is carried out for a period of from 2 hours to 64 hours.

[0131]

[0139] Embodiment 29: The method of any of the previous or following embodiments, wherein the baking step is carried out for a period of 8 hours to 16 hours.

[0132]

[0140] Embodiment 30: The method of any of the preceding or following embodiments, wherein the step of milling the YAG compact includes the compact and the solvent being contained in a polymer-coated milling vessel.

[0133]

[0141] Embodiment 31: The method of any of the preceding or following embodiments, wherein the solvent is ethanol alcohol or isopropyl alcohol.

[0134]

[0142] Embodiment 32: The method of any of the preceding or following embodiments, wherein the step of milling the YAG compact comprises milling for at least 6 hours.

[0135]

[0143] Embodiment 33: The method of any of the preceding or following embodiments, wherein the step of milling the YAG compact includes the YAG compact material self-fracturing to produce a YAG powder having an average particle size distribution of less than 100 μm.

[0136]

[0144] Embodiment 34: The method of any of the preceding or following embodiments, wherein the average particle size distribution is less than 63 μm.

[0137]

[0145] Embodiment 35: The method of any of the preceding or following embodiments, wherein the average particle size distribution is less than 44 μm.

[0138]

[0146] Embodiment 36: The method of any of the preceding or following embodiments, wherein the milled YAG compacted material is sieved before drying.

[0139]

[0147] Embodiment 37: The method of any of the preceding or following embodiments, wherein the YAG powder has a bimodal particle size distribution.

[0140]

[0148] Embodiment 38: The method of any of the preceding or following embodiments, wherein drying is performed at a temperature of less than 90° C.

[0141]

[0149] Embodiment 39: A method of synthesizing a doped yttrium aluminum garnet (YAG) powder, comprising: providing powders of yttria, silica, and at least one dopant formed of an oxide, hydrate, nitrate, or chloride of a lanthanide or transition metal, and mixing to form a powder mixture, where no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media and a solvent to form a powder slurry; adding an organic binder to the powder slurry and mixing to form a sprayable powder slurry; spray drying the sprayable powder slurry to form a spray-dried powder; compacting the spray-dried powder to 35% or less of theoretical density to form a powder compact; firing the powder compact in air to 50% or less of theoretical density to form a YAG compact; and milling the YAG compact without grinding media and then drying to produce a doped YAG powder.

[0142]

[0150] Embodiment 40: Y 3 Al 5 O 12 and less than 3 wt.% additional Al 2 O 3 A yttrium aluminum garnet (YAG) composition comprising: 2 O 3 A composition comprising an eroded portion of an alumina grinding media.

[0143]

[0151] Embodiment 41: The composition of any of the preceding or following aspects, further comprising a dopant concentration of at least 1 atomic %.

[0144]

[0152] Embodiment 42: A phosphor wheel or LED light comprising the composition of any of the preceding aspects.

[0145]

[0153] In the following description, specific terminology is used for the sake of clarity, but these terminologies are intended only to indicate the particular structure of the embodiments selected for illustration in the drawings, and are not intended to define or limit the scope of the present disclosure. In the drawings and the following description, it should be understood that like numerical designations refer to components of similar functionality.

[0146]

[0154] Unless the context clearly indicates otherwise, the singular forms "a," "an," and "the" include plural referents as well.

[0147]

[0155] As used in the specification and claims, the term "comprising" may include the specific expressions "consisting of" and "consisting essentially of." The terms "comprising," "including," "having," "has," "can," "containing," and variations thereof, as used herein, are intended to be open-ended transitional phrases, terms, or words that require the presence of the specified components / ingredients / steps and permit the presence of other components / ingredients / steps. However, such descriptions should also be construed as describing compositions, articles, or methods that "consist of" and "consist essentially of" the listed components / ingredients / steps, which permit the presence of only the specified components / ingredients / steps and any impurities that may result therefrom, and exclude other components / ingredients / steps.

[0148]

[0156] Numerical values ​​in the specification and claims of this application should be understood to include numerical values ​​that are the same when rounded to the same number of significant digits, and numerical values ​​that differ from the stated value by less than experimental error of conventional measuring techniques of the type described in this application to determine the value.

[0149]

[0157] All ranges disclosed herein are inclusive of the recited endpoints and are independently combinable (e.g., the range "2 grams to 10 grams" includes the endpoints of 2 grams or 10 grams, and all intermediate values).

[0150]

[0158] When a material is described as having an average particle size or an average particle size distribution, this is defined as the particle diameter at which a cumulative percentage of 50% (by volume) of the total number of particles is achieved. In other words, 50% of the particles have a diameter greater than the average particle size and 50% of the particles have a diameter less than the average particle size. The particle size distribution is Gaussian, with upper and lower quartiles at 25% and 75% of the stated average particle size, and all particles are less than 150% of the stated average particle size.

[0151]

[0159] Method steps described herein refer to temperatures and, unless specified, refer to the temperature achieved by the referenced material, not the temperature to which a heat source (e.g., furnace, oven) is set. The term "room temperature" refers to the range of 20°C to 25°C (68°F to 77°F).

[0152]

[0160] The term "about" can be used to include any numerical value that can vary without changing the base function of its value. When used in conjunction with a range, "about" also discloses a range defined by the absolute values ​​of the two endpoints, for example, "about 2 to about 4" also discloses a range of "2 to 4." The term "about" can refer to plus or minus 10% of the indicated number.

[0153]

[0161] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be readily apparent to those skilled in the art. In view of the above discussion, the relevant knowledge in the art, and the references discussed above in conjunction with the background art and the detailed description, the disclosures of which are all incorporated herein by reference. Furthermore, it should be understood that the aspects of the present invention and parts and various features of the various embodiments recited below and / or in the appended claims can be combined or exchanged in whole or in part. In the above description of various embodiments, those embodiments that refer to other embodiments can be appropriately combined with other embodiments as understood by those skilled in the art. Furthermore, those skilled in the art will understand that the above description is for illustrative purposes only and is not intended to be limiting. Specific embodiments of the present invention are as follows. [Aspect 1] 1. A method for synthesizing yttrium aluminum garnet (YAG) powder, comprising the steps of: introducing yttria and silica powders to form a powder mixture, wherein no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media and a solvent to form a powder slurry; processing the powder slurry to form a green compact; The green compact is sintered in air at a temperature of 1100°C to 1650°C for more than 8 hours to a density of 50% or less of theoretical density, and at least 92% by weight of Y is obtained. 3 Al 5 O 12 forming a yttrium aluminum garnet compact of milling the yttrium aluminum garnet compact without grinding media and then drying to produce the yttrium aluminum garnet powder; A method comprising: [Aspect 2] 2. The method of claim 1, wherein the processing step comprises spray drying the powder slurry to form a spray-dried powder and consolidating the spray-dried powder to up to 35% of theoretical density to form a compact. [Aspect 3] 2. The method of embodiment 1, wherein the calcining step is carried out at a temperature between 1450° C. and 1550° C. for a period of 8 hours to 16 hours. [Aspect 4] 2. The method of embodiment 1, wherein the yttrium aluminum garnet powder is sinterable to greater than 96% of theoretical density. [Aspect 5] The alumina grinding medium is 95.0 to 99.8% Al 2 O 3 and the composition after ball milling is stoichiometric 3Y 2 O 3 :5Al 2O 3 and less than 3 wt.% additional Al 2 O 3 2. The method of embodiment 1, comprising: [Aspect 6] The additional Al 2 O 3 comprises an eroded portion of the alumina grinding media. [Aspect 7] 2. The method of claim 1, wherein the step of milling the yttrium aluminum garnet compact comprises the yttrium aluminum garnet compacted material being self-fracturing to produce the yttrium aluminum garnet powder having an average particle size distribution of less than 100 μm. [Aspect 8] The powder to be introduced further comprises a dopant comprising a lanthanide or a transition metal, the lanthanide or the transition metal being in the form of a compound, the compound being an oxide, a hydrate, a nitrate, a chloride, or a combination thereof, or the compound being ceria (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 ·7H 2 O), or cerium(III) nitrate hexahydrate (Ce(NO 3 ) 3 ·6H 2 O). [Aspect 9] The method of embodiment 8, wherein the lanthanide or transition metal is ionized to +3 and has an ionic radius of 0.114 nm or less. [Aspect 10] 9. The method of embodiment 8, wherein the lanthanide or transition metal comprises scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or a combination thereof, or the lanthanide or transition metal is scandium, zinc, or cerium. [Aspect 11] 9. The method of claim 8, wherein the dopant is from 10 ppm to 6 wt.%, based on the total weight of the powder mixture; or the dopant is from 0.1 wt.% to 5 wt.%, based on the total weight of the powder mixture, of ceria. [Aspect 12] 12. The method of claim 11, wherein the dopant is less than 3 wt.% ceria, based on the total weight of the powder mixture. [Aspect 13] 2. The method of claim 1, wherein the yttria powder has a purity of 2N or greater, or has a purity of 3N or greater, and the silica is 0.1% to 0.3% by weight, based on the total weight of the powder mixture. [Aspect 14] 1. A method for synthesizing a doped yttrium aluminum garnet (YAG) powder, comprising: introducing and mixing powders of yttria, silica, and at least one dopant formed of an oxide, hydrate, nitrate, or chloride of a lanthanide or transition metal to form a powder mixture, wherein no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media and a solvent to form a powder slurry; processing the powder slurry to form a green compact; The green compact is sintered in air at a temperature of 1100°C to 1650°C for more than 8 hours to a density of 50% or less of theoretical density, and at least 92% by weight of Y is obtained. 3 Al 5 O 12 forming a yttrium aluminum garnet compact of milling the yttrium aluminum garnet compact without grinding media and then drying to produce the doped yttrium aluminum garnet powder; A method comprising: [Aspect 15] 1. A yttrium aluminum garnet (YAG) composition comprising: 94% to 100% by weight Y 3 Al 5 O 12 、 0% to 3% by weight of a dopant, and 0% to 3% by weight of Al 2 O 3 and additional Al 2 O 3 comprises an eroded portion of the alumina grinding media.

Claims

1. 1. A method for synthesizing yttrium aluminum garnet (YAG) powder, comprising the steps of: introducing yttria and silica powders to form a powder mixture, wherein no alumina is added to the powder mixture; ball milling the powder mixture in the presence of alumina grinding media as the sole source of alumina and a solvent to form a powder slurry; processing the powder slurry to form a green compact; The green compact is sintered in air at a temperature of 1100° C. to 1650° C. for 8 hours or more to a density of 50% or less of theoretical density, and at least 92% by weight of Y is obtained. 3 A 5 O 12 forming a yttrium aluminum garnet compact of milling the yttrium aluminum garnet compact without grinding media and then drying to produce the yttrium aluminum garnet powder; A method comprising:

2. 10. The method of claim 1, wherein the processing step comprises spray drying the powder slurry to form a spray-dried powder and compacting the spray-dried powder to 35% or less of theoretical density to form a compact.

3. The method of claim 1, wherein the firing step is carried out at a temperature between 1450° C. and 1550° C. for a period of between 8 hours and 16 hours.

4. 10. The method of claim 1, wherein the yttrium aluminum garnet powder is sinterable to greater than 96% of theoretical density.

5. The alumina grinding media is 95.0 to 99.8% Al 2 O 3 and the composition after ball milling has a purity of stoichiometric 3Y 2 O 3 : 5Al 2 O 3 and less than 3 wt.% additional Al 2 O 3 The method of claim 1 , comprising:

6. The additional Al 2 O 3 The method of claim 5 , wherein comprises an eroded portion of the alumina grinding media.

7. 2. The method of claim 1, wherein the step of milling the yttrium aluminum garnet compact comprises the yttrium aluminum garnet compact material being self-fragmenting to produce the yttrium aluminum garnet powder having an average particle size distribution of less than 100 microns.

8. The powder to be introduced further comprises a dopant comprising a lanthanide or a transition metal, the lanthanide or the transition metal being in the form of a compound, the compound being an oxide, a hydrate, a nitrate, a chloride, or a combination thereof, or the compound being ceria (CeO 2 ), cerium(III) chloride heptahydrate (CeCl 3 ・7H 2 O), or cerium(III) nitrate hexahydrate (Ce(NO 3 ) 3 ・6H 2 The method of claim 1, wherein

9. 9. The method of claim 8, wherein the lanthanide or transition metal is ionized to +3 and has an ionic radius of 0.114 nm or less.

10. 9. The method of claim 8, wherein the lanthanide or transition metal comprises scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, silver, cadmium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or a combination thereof, or the lanthanide or transition metal is scandium, zinc, or cerium.

11. 9. The method of claim 8, wherein the dopant is from 10 ppm to 6 wt. % based on the total weight of the powder mixture, or the dopant is from 0.1 wt. % to 5 wt. % ceria based on the total weight of the powder mixture.

12. 12. The method of claim 11, wherein the dopant is less than 3 wt% ceria, based on the total weight of the powder mixture.

13. 2. The method of claim 1, wherein the yttria powder has a purity of 2N or higher, or a purity of 3N or higher, and the silica is 0.1% to 0.3% by weight based on the total weight of the powder mixture.

14. 1. A method for synthesizing a doped yttrium aluminum garnet (YAG) powder, comprising: introducing and mixing powders of yttria, silica, and at least one dopant formed of an oxide, hydrate, nitrate, or chloride of a lanthanide or transition metal to form a powder mixture, wherein no alumina is added to said powder mixture; ball milling the powder mixture in the presence of alumina grinding media as the sole source of alumina and a solvent to form a powder slurry; processing the powder slurry to form a green compact; The green compact is sintered in air at a temperature of 1100° C. to 1650° C. for 8 hours or more to a density of 50% or less of theoretical density, and at least 92% by weight of Y is obtained. 3 A 5 O 12 forming a yttrium aluminum garnet compact of milling the yttrium aluminum garnet compact without grinding media and then drying to produce the doped yttrium aluminum garnet powder; A method comprising:

15. The method of claim 1, wherein the alumina grinding media has a purity of 95.0% to 99.99% Al 2 O 3 .

16. The method of claim 1, wherein the ball milling is performed in a polymer-coated ball milling vessel or in a non-reactive vessel.

Citation Information

Patent Citations

  • Method for determining raw material ratio in preparation process of optical ceramics

    CN108536993A

  • Eu-CONTAINING INORGANIC COMPOUND, LUMINESCENT COMPOSITION CONTAINING THE SAME AND ILLUMINANT, SOLID-STATE LASER APPARATUS AND LIGHT EMITTING DEVICE

    JP2007254723A

  • Method for manufacturing transparent ceramics for faraday rotator

    JP2019207340A

  • Ce;LuAP BAKING BODY, POSITRON FAULT-MEASURING APPARATUS, AND METHOD FOR PRODUCING THE BAKING BODY

    JP2020200206A

  • Light wavelength conversion member and light-emitting device

    WO2020026819A1